A atratividade da capa do livro no meio online - Cardozo, Missila Loures (2005)
This work aimed to understand the cover of the book as its "packaging", with its persuasive characteristics within e-commerce (potential market in development) and how the consumer behaves in online and offline purchases. Analysis of the book cover design and the use of persuasive techniques to enhance its decoding, as well as its importance in the act of traditional or online shopping. This research is based on bibliographic survey and field research (experiment), in order to contemplate both the theoretical and the factual aspects. The bibliographic survey presented aspects of the history of the book, the editorial process, the mechanisms of visual attractiveness and their psychological bases, consumer behavior and e-commerce characteristics served as a foundation to understand the context in which the object of study of this work, the covers of the books, is inserted. The experiment aimed to verify if there are aesthetic standards that provide greater attractiveness in the online environment and, consequently, which characteristics are most striking for this receiver. In general, this work can point out that the presence of the book cover in e-commerce is of fundamental importance in the consumer's decision, and can even generate impulse purchases, and that the image is the most important element in the composition of a cover. (AU)